A prospective study on sucrose consumption, visible plaque and caries in children from 3 to 6 years of age - Karjalainen S, Söderling E, Sewo´n L, Lapinleimu H, Simell O (Blackwell Synergy, 2001)
As data on the association of sugar consumption and dental caries in the industrialized countries give mixed results, we prospectively studied this association in 135 healthy Finnish children (71 boys, 64 girls).